Is the Design Studio Dead? - An International Perspective on the Changing Shape of the Physical Studio across Design Domains - Fleischmann, Katja (Design and Technology Education: An International Journal, 2021)
The process of moving the physical design studio experience, where social interaction is a guiding principle, into a detached virtual environment during the Covid pandemic has prompted design educators to re-evaluate what constitutes a traditional studio-based learning system. This shift is based on classroom experiences after design educators moved their courses online as physical classrooms closed. Early research findings indicate that design educators and students adapted surprisingly well to an online classroom during the pandemic. But is this equally the case across all design domains? The author argues that it is unhelpful to generalise across design domains when setting out to construct alternative digital learning and teaching environments. This study contextualises varying responses to the online design studio and offers a unique international perspective on differences in design domains impacting future plans to offer blended or online learning. The research is underpinned by the epistemology of pragmatism. The interpretation of data is based on surveys filled out by 90 highly experienced design educators representing eight design domains in seven countries. Results indicate a clear shift toward long-term acceptance of select online elements even in design domains focused on physical studio skills. It is clear that design domains will differ in their adoption and development of blending face-to-face and online teaching in the future.